2017
DOI: 10.1007/s13402-017-0324-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis: Putative therapeutic role of vascular cell adhesion molecule-1

Abstract: This study focuses on recent progress on the role of VCAM-1, an important glycoprotein belonging to the immunoglobulin (Ig) superfamily of cell surface adhesion molecules in breast cancer angiogenesis, survival and metastasis. Targeting VCAM-1, expressed on the surface of breast cancer cells, and/or its specific ligand VLA-4/α4β1 integrin, expressed on cells at the site of metastasis, may be a useful strategy to reduce breast cancer cell invasion and metastasis. Various approaches to therapeutically target VCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 73 publications
1
68
0
1
Order By: Relevance
“…Uncoupling of M-E reversion from FN expression explains why FN high tumor cells can repeatedly be isolated from macrometastatic foci in distant organs [77]. Such phenomenon also explains well why DTCs outgrown in the first metastatic site can reenter the circulation and colonize the second metastatic site [349,350], likely through reversible E-M and M-E plasticity without affecting periFN assembly on their cell surfaces. Aforementioned interchanges of various phenotypes in tumor cells, stromal cells, and stromal FN during the whole processes of tumor genetic/epigenetic evolution and progression where hypoxia and PMN are critically at the crossroads are illustrated in Figure 4.…”
Section: Malignant Tumor Cells In the Primary Tissues Early Establishmentioning
confidence: 98%
“…Uncoupling of M-E reversion from FN expression explains why FN high tumor cells can repeatedly be isolated from macrometastatic foci in distant organs [77]. Such phenomenon also explains well why DTCs outgrown in the first metastatic site can reenter the circulation and colonize the second metastatic site [349,350], likely through reversible E-M and M-E plasticity without affecting periFN assembly on their cell surfaces. Aforementioned interchanges of various phenotypes in tumor cells, stromal cells, and stromal FN during the whole processes of tumor genetic/epigenetic evolution and progression where hypoxia and PMN are critically at the crossroads are illustrated in Figure 4.…”
Section: Malignant Tumor Cells In the Primary Tissues Early Establishmentioning
confidence: 98%
“…Vascular cell adhesion molecule-1 (VCAM-1) is aberrantly expressed in breast cancer cells and binds to a4b1 integrin, which also interacts with fibronectin and is expressed in natural killer cells, monocytes, and other immune cells. 131 It was shown that the pulmonary parenchyma containing collagen and elastin fibers acts as a preferable soil for the homing of VCAM-1-expressing breast cancer. 132 …”
Section: Extracellular Matrix (Ecm) Proteinsmentioning
confidence: 99%
“…Cancer metastasis is one of the major causes of cancer‐related deaths . During metastasis, primary tumor cells migrate from the parent tumor into neighboring tissues to form secondary tumors .…”
Section: Introductionmentioning
confidence: 99%